The Oxford companion to the Earth - Hancock, Paul L.; Skinner, Brian J., 1928-; Oxford University Press (Oxford : Oxford University Press, 2000)
This reference work, offers coverage of the earth sciences, from volcanoes to flood plains, diamonds to meteors, deserts to deep seas. All aspects of geology, including climatology, mineralogy, and oceanography, are covered.
"Oxford Reference Online Premium."
Title from home page (viewed on Dec. 22, 2009).
Also issued in print format.
Mode of access: World Wide Web.
Keywords: Earth sciences -- Encyclopedias